2015
DOI: 10.1007/s00347-015-0073-z
|View full text |Cite
|
Sign up to set email alerts
|

Ocriplasmin zur Behandlung der symptomatischen vitreomakulären Traktion mit und ohne Makulaforamen

Abstract: In this ongoing study there was a high percentage of resolution of vitreomacular traction (71 %) 1 month after intravitreal operative injection of Jetrea® and closure of two out of five macular holes. This was further associated with stabilization of visual acuity and reduction of foveal thickness. Further investigations are necessary to document the effectiveness of the pharmacological vitreolysis in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…We found higher VMT release rates than the MIVI-TRUST trials (56.6 vs. 26.5%) that are in line with previous series investigated by several authors with release rates ranging from 30 to 71% [7,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29] and may arise from a favorable patient sample: few patients with ERM (11.0%), only 3.6% of patients with adhesion diameter >1,500 µm and 72.3% of patients with phakic eyes. In fact, 12 eyes in our sample fitted the ideal characteristics described by Haller et al [13] (age <65 years, absence of ERM, phakic, adhesion diameter ≤1,500 µm and FTMH ≤250) and had a release rate of 91.7% (n = 11).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We found higher VMT release rates than the MIVI-TRUST trials (56.6 vs. 26.5%) that are in line with previous series investigated by several authors with release rates ranging from 30 to 71% [7,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29] and may arise from a favorable patient sample: few patients with ERM (11.0%), only 3.6% of patients with adhesion diameter >1,500 µm and 72.3% of patients with phakic eyes. In fact, 12 eyes in our sample fitted the ideal characteristics described by Haller et al [13] (age <65 years, absence of ERM, phakic, adhesion diameter ≤1,500 µm and FTMH ≤250) and had a release rate of 91.7% (n = 11).…”
Section: Discussionsupporting
confidence: 80%
“…In the MIVI-TRUST trials, 40.6% of FTMH achieved closure, while recent series achieved closure rates of 13-80% [14,15,16,17,20,21,22,23,24,25,26,27,28,29,31]. In our study, 50.0% of eyes with FTMH achieved closure, while most of them, 83%, achieved VMT resolution as well.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Clinical reports and small case series raised concern on potential side effects of the enzyme. These studies reported on clinical symptoms and findings including varying degrees of retinal dysfunction, such as visual acuity loss, dyschromatopsia, nyctalopia, visual field constriction, outer retinal signal abnormalities or defects on spectral domain optical coherence tomography, macular hole enlargement, macular detachment with subretinal fluid accumulation, and electroretinography changes [6,7,12,13,14,19,20,21,22,23,24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…Compared to pars plana vitrectomy with peeling of the internal limiting membrane (ILM), which was the only treatment option until recently, intravitreal ocriplasmin injection provides a generally well-tolerated therapeutic intervention for patients with VMT [6,7]. There are numerous potential advantages of pharmacologic vitreolysis over surgical vitrectomy, such as avoidance of surgical risks, faster visual rehabilitation, and induction of a complete posterior vitreous detachment without remnants of vitreous cortex collagen on the ILM.…”
Section: Introductionmentioning
confidence: 99%